2016
DOI: 10.1007/s10614-016-9600-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversification Measures and the Optimal Number of Stocks in a Portfolio: An Information Theoretic Explanation

Abstract: The views expressed are those of the author(s) and do not necessarily represent those of the funder, ERSA or the author's affiliated institution(s). ERSA shall not be liable to any person for inaccurate information or opinions contained herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…Based on modern portfolio theory by Harry Markowitz (1952), investors are advised not to invest only in one security, but to spread their investment in several securities, thus it is necessary for investors to form a portfolio through a combination of a number of stocks to minimize risk without reducing the expected return. This is confirmed by the statement of Oyenubi (2019) that increasing the number of shares in the portfolio can increase the level of diversification and have an impact on reducing portfolio risk.…”
Section: Introductionsupporting
confidence: 52%
“…Based on modern portfolio theory by Harry Markowitz (1952), investors are advised not to invest only in one security, but to spread their investment in several securities, thus it is necessary for investors to form a portfolio through a combination of a number of stocks to minimize risk without reducing the expected return. This is confirmed by the statement of Oyenubi (2019) that increasing the number of shares in the portfolio can increase the level of diversification and have an impact on reducing portfolio risk.…”
Section: Introductionsupporting
confidence: 52%
“…Most of the studies dealing with the necessary number of stocks to diversify the unsystematic risk were mainly conducted in the U.S. market (Evans and Archer 1968;Fielitz 1974;Statman 1987;Beck et al 1996;O'Neal 1997;Barber and Odean 2000;Statman 2002;Domian et al 2007;Benjelloun 2010;Diyarbakırlıo glu and Satman 2013;Alexeev and Tapon 2014;Zhou 2014;Oyenubi 2019;Kurtti 2020), while few have attempted to investigate this issue in other (underdeveloped) markets (Gupta and Khoon 2001;Brands and Gallagher 2005;Irala and Patil 2007;Alekneviciene et al 2012;Stotz and Lu 2014;Ahuja 2015;Bradfield and Munro 2017;Murthy 2018;Raju and Agarwalla 2021). Based on the results, most studies in the past have used the variance or standard deviation of returns as a metric to assess risk reduction (Evans and Archer 1968;Solnik 1974;Statman 1987;Beck et al 1996), and this has continued to be the authors' first choice in recent years (Brands and Gallagher 2005;Benjelloun 2010).…”
Section: Number Of Stocks Required For Risk Diversificationmentioning
confidence: 99%
“…Just for comparison, early studies based on (semi-)annual and quarterly data have shown that 8 to 16 stocks are sufficient for optimal diversification (Evans and Archer 1968;Fielitz 1974;Zhou 2014). Some have used monthly data (Statman 1987;Beck et al 1996;Gupta and Khoon 2001;Statman 2002;Tang 2004;Brands and Gallagher 2005;Irala and Patil 2007;Dbouk and Kryzanowski 2009;Benjelloun 2010;Kryzanowski and Singh 2010;Stotz and Lu 2014;Kisaka et al 2015;Haensly 2020;Raju and Agarwalla 2021), but also weak data (Solnik 1974;Bradfield and Munro 2017;Oyenubi 2019;Lee et al 2020) or even daily data (Domian et al 2007;Alekneviciene et al 2012;Alexeev and Tapon 2012;Chong and Phillips 2013;Ahuja 2015). As Alexeev and Dungey (2015) further point out, high-frequency data undeniably improves risk assessment and brings significant benefits to decisionmaking.…”
Section: -50 Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Their problem is verified by existed stock returns data, and results show the MDI can be powerfully applied to define a large set of investable assets. Oyenubi (2016) reported an acceptable description for the elusiveness of the optimum amount of stocks in a portfolio. He used the Portfolio Diversification Index (PDI) to quantify diversification.…”
Section: Research Backgroundmentioning
confidence: 99%